Study of CP asymmetry in B0-B0 mixing with inclusive dilepton events - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review letters, 2015)
We present a measurement of the asymmetry ACP between same-sign inclusive dilepton samples ℓ+ℓ+ and ℓ−ℓ− (ℓ=e, μ) from semileptonic B decays in Υ(4S)→B¯B events, using the complete data set recorded by the BABAR experiment near the Υ(4S) resonance, corresponding to 471×106 B¯B pairs. The asymmetry ACP allows comparison between the mixing probabilities P(¯B0→B0) and P(B0→¯B0), and therefore probes CP and T violation. The result, ACP=[−3.9±3.5(stat)±1.9(syst)]×10−3, is consistent with the standard model expectation.